Pemberdayaan Sumber Daya Manusia Berbasis Motivasi Kerja melalui Pendekatan ABCD dalam Meningkatkan Produktivitas Masyarakat di Era Transformasi Digital - Asa'ari, Asa'ari; Yani, Ahmad; Handican, Rhomiy; Gunawan, Rilla Gina (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2025)
Digital transformation requires communities to possess adaptive capabilities, work motivation, and high productivity in responding to social and economic changes. However, many communities are still unable to optimally utilize digital technology due to low work motivation, limited digital literacy, and weak productivity management. This community service program aimed to enhance human resource capacity based on work motivation through the Asset-Based Community Development approach to support community productivity in the digital transformation era. The implementation method employed the ABCD approach through the stages of discovery, dream, design, define, and destiny. The program was conducted through work motivation training, time management training, digital technology utilization training, and productivity development assistance for the community. Data collection techniques included observation, interviews, documentation, and participatory evaluation. The results demonstrated an improvement in community work motivation, time management skills, and the utilization of digital media to support productive activities and business development. In addition, the ABCD approach succeeded in increasing community participation and optimizing local assets as sustainable capital for human resource development. This program positively contributed to improving community productivity and strengthening community capacity in facing the challenges of digital transformation independently and sustainably